Pastoral Care and Counseling in a Cross-Cultural Context: The Issue of Authority - Bryant, Cullene (The Journal of pastoral care, 1995)
Reflects on a personal teaching experience in the Philippines and notes some of the perspectival differences in assumptions undergirding pastoral care practice, particularly regarding issues of authority.